2020
DOI: 10.17221/252/2020-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the effects of relevant factors on Pakistan's agricultural products export

Abstract: Pakistan is an agriculture-based country, so the agricultural sector is known as the backbone of the national economy. Considering the national economy and the agricultural industry, it is necessary to focus on earnings through agricultural products export to improve the livelihood of local farmers. Therefore, the current study aimed to analyse the short-term and long-term factors affecting agricultural products export. The annual time series of 1976–2016 were collected from World Bank indicators, the Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…Our results of the regression analysis of the impact of the sown land area on the wheat exports volume are in line with a similar study conducted by Khan et al (2020). They confirmed the short-term correlation between sown areas and crop production in terms of agricultural exports and between employment in agriculture and exports of agricultural products.…”
Section: Fig 8 Impact Of Wheat Cultivation Area On the Volume Of Its ...supporting
confidence: 91%
See 1 more Smart Citation
“…Our results of the regression analysis of the impact of the sown land area on the wheat exports volume are in line with a similar study conducted by Khan et al (2020). They confirmed the short-term correlation between sown areas and crop production in terms of agricultural exports and between employment in agriculture and exports of agricultural products.…”
Section: Fig 8 Impact Of Wheat Cultivation Area On the Volume Of Its ...supporting
confidence: 91%
“…Firlej and Kubala (2018) understand the export potential as the competitive advantages of the country in the production of certain types of agricultural products. Khan et al (2020) view export potential as an opportunity to increase agricultural production and exports in response to growing aggregate demand for it in domestic or international markets.…”
Section: Fig 1 Abstract Research Designmentioning
confidence: 99%
“…Testing stationarity is vital for both time and panel data because non-stationary data lead to spurious results [49]. Thus, Im, Pesaran, and Shin's test [50] for unit roots was applied to test the stationarity [51][52][53]. However, it has been argued that such unit root tests for panel data may not be accurate due to the probability of cross-sectional dependency.…”
Section: Model Specificationmentioning
confidence: 99%
“…The economic theory specifies that trade and foreign direct investment (FDI) lead to development and growth, especially in underdeveloped and emerging countries. Khan et al [16] found that export of agricultural products improves the livelihood of local farmers. Trade liberalization and FDI across borders have formed several ecological challenges, locally and globally, through anthropogenic activities such as the rise in energy consumption, population growth, and economic growth and development [17].…”
Section: Introductionmentioning
confidence: 99%